Keterkaitan Warna Desain Kemasan dan Daya Tarik Generasi Z terhadap Produk Teh Celup - Clara Lidwina Larasati; Brigitta Eliza Nadia Kusuma; Regina Jovanytha Zefanya Liwoso; Sri Hapsari Wijayanti (Jurnal Simki Economic, 2024)
One of the important visual branding elements in marketing strategy is color quality. This study aims to analyze the relationship between the use of color in the packaging design of tea bags, especially Sosro, SariWangi, and Poci, with consumer attractiveness so as to influence purchase intention. This research uses a quantitative method by distributing a google form with a four-option Likert scale to thirty active students of the Faculty of Economics and Business in one of university in Jakarta. The questionnaire contains eleven closed questions and one open question which are then analyzed descriptively quantitatively. The results of this study show that there is a relationship between the use of packaging colors for tea bags and consumer appeal, especially generation Z. The color combination on SariWangi provides greater appeal than Sosro, but does not differ much from the appeal of Teh Poci. The color combination on SariWangi shows an atmosphere of calmness, while The Poci gives an atmosphere of cheerfulness and freshness. These colors predominantly reflect generation Z who are active, cheerful, and dynamic, but love serenity.